2019
DOI: 10.2134/cftm2018.12.0097
|View full text |Cite
|
Sign up to set email alerts
|

Nutritive Value Change during the Fall of Late-Summer-Planted Oats, Radishes, and Turnips

Abstract: Core Ideas• Nutritive value of late-summer-planted oats, radishes, and turnips is high in early fall.• Oats, radishes, and turnips maintain a high nutritive value through early winter.• Brassicas remain high in sulfur through the fall with potential for toxicity. AbstractThe change in nutritive value of late-summer-planted oats (Avena sativa L.) and brassicas (Brassica spp.) during the fall in the Midwestern US is not well documented. A mixture of 'Jerry' oats, 'daikon' oilseed radish (Raphanus sativus L.), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 22 publications
1
3
2
Order By: Relevance
“…Oat IVOMD decreased linearly ( P = 0.02) over the grazing season from approximately 65% to 48% ( Figure 5 ). This agrees with previous research ( Lenz et al, 2019 ), which reported decreased IVOMD in January (67.4%) compared to October (79.0%) for oats planted in late August and early September. In the current experiment, crude protein for mid-August planted oats decreased quadratically ( P = 0.04) over the grazing season from approximately 11% to 6% ( Figure 6 ).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Oat IVOMD decreased linearly ( P = 0.02) over the grazing season from approximately 65% to 48% ( Figure 5 ). This agrees with previous research ( Lenz et al, 2019 ), which reported decreased IVOMD in January (67.4%) compared to October (79.0%) for oats planted in late August and early September. In the current experiment, crude protein for mid-August planted oats decreased quadratically ( P = 0.04) over the grazing season from approximately 11% to 6% ( Figure 6 ).…”
Section: Resultssupporting
confidence: 93%
“…In the current experiment, crude protein for mid-August planted oats decreased quadratically ( P = 0.04) over the grazing season from approximately 11% to 6% ( Figure 6 ). Lenz et al (2019) did not observe a change in CP of oats, ranging of 13.8% to 17.9%, for oats planted in late August and early September. The higher IVOMD and CP values reported by Lenz et al (2019) may be due to later planting dates compared to the current experiment.…”
Section: Resultscontrasting
confidence: 57%
See 2 more Smart Citations
“…Generally, the yield advantage before winter that is associated with these differences in developmental physiology is approximately 2:1 (Coblentz & Walgenbach, 2010; Gunsaulis et al., 2008). Some studies have also included other forages, such as other cereals, radish ( Raphanus sativus L.), or turnip ( Brassica rapa L.), within mixed‐species evaluations that included oat (Lenz, Cox‐O'Neill, Hales, & Drewnoski, 2019; Maloney et al., 1999). Other advantages of using oat for autumn forage production include reduced lignification, improved fiber digestibility, accumulation of water‐soluble carbohydrates in response to frost events, and general stabilization of energy density over a wide time interval for potential mechanical harvest as silage or utilization by grazing livestock (Coblentz & Walgenbach, 2010; Coblentz et al., 2013; Coblentz, Bertram, Martin, & Berzaghi, 2012).…”
Section: Introductionmentioning
confidence: 99%